Understanding hydrological variability for improved water management in the semi-arid Karkheh Basin, Iran - Masih, I. (2011)
This study is carried out in semi-arid to arid Karkheh Basin of Iran, where massive water allocation planning is on the way, but a comprehensive knowledge on basin hydrology and impact of these developments on different water uses and users across the basin are lacking. The main objective of this research is to provide a hydrology-based assessment of (surface) water resources of the Karkheh Basin and study its continuum of variability and change at different spatio-temporal scales. The methodological framework used in this study was underpinned by the combined use of rigorous system investigation and hydrological modeling echniques. The spatial investigations were carried out at the levels of the river basin, catchment (subbasin) and subcatchment whereas the temporal resolutions were daily, monthly, annually and in long-term time series.